The use of local and nonlocal priors in Bayesian test‐based monitoring for single‐arm phase II clinical trials. (19th May 2021) - Zhou, Yanhong; Lin, Ruitao; Lee, J. Jack
Abstract: Bayesian sequential monitoring is widely used in adaptive phase II studies where the objective is to examine whether an experimental drug is efficacious. Common approaches for Bayesian sequential monitoring are based on posterior or predictive probabilities and Bayesian hypothesis testing procedures using Bayes factors. In the first part of the paper, we briefly show the connections between test‐based (TB) and posterior probability‐based (PB) sequential monitoring approaches. Next, we extensively investigate the choice of local and nonlocal priors for the TB monitoring procedure. We describe the pros and cons of different priors in terms of operating characteristics. We also develop a user‐friendly Shiny application to implement the TB design.